Post gastrectomy gastrojejunocolic fistula.: about a case - Piñeyro, Alberto; Rodríguez, José L; Cidade, Luis; Bergalli, Luis (Cirugía del Uruguay, 1985)
Description of a case of gastrojejunocolic fistula occurring six years alter gastrectomy performed on account of duodenal ulcus, resolved satisfactory in a single surgical intervention. A brief review of the subject is made, specially its etiologic and therapeutic aspects.